Fatigue assessment of 3D-printed porous PLA-based scaffold structures by Thermographic Methods. Issue 1 (1st February 2023) - Ahmadi, R; D'Andrea, D; Santonocito, D
Abstract: Additive manufacturing with Fused Deposition Modelling (FDM) provides new opportunities for biomedical applications by manufacturing more complex structure for tissue scaffolds. In contrast to traditionally manufacturing methods such as injection moulding, FDM-made structures are produced with layer-by-layer adhesion mechanism. Moreover, setting different parameters is critically important to obtain reliable components, consequently fatigue analysis of these structures gets complicated. Therefore, a scaffold must be designed to replace human bone and withstand to static and fatigue loads. Although PLA scaffolds fabricated by FDM have been widely investigated, the fatigue behaviors research on them have been narrowly published; therefore, it is necessary to analyze the fatigue behaviour of PLA scaffolds because of their wide application in medical science. In this study, fatigue analysis of scaffolds-like specimens made by PLA is carried out by monitoring the energy release of such structures. Thermographic Methods are applied to obtain, in a short time and with few materials' consumption, fatigue life information of scaffold-like structures produced with different printing parameters.